O CIRCO NA HISTÓRIA: A PLURALIDADE CIRCENSE E AS REVOLUÇÕES FRANCESA E SOVIÉTICA [Mario Fernando Bolognesi] - Repertório, Teatro & Dança (Repertório, 2010)
Este artigo trata do circo como arte plural, que tende a reafirmar a supremacia do homem diante dos animais e da natureza, através da exposição espetacular das suas habilidades. O circo é por excelência o espetáculo da maioridade humana na história, cabendo ressaltar dois momentos históricos em que as artes circenses foram apropriadas: as revoluções francesa e russa. This article deals with the circus as plural art, which tends to testify the supremacy of human being before the animals and nature through the spectacular display of his skills. The circus is par excellence the spectacle of human majority in history, it is worth highlighting two historical moments in which the circus was appropriate: the French and Russian revolutions.